2010
DOI: 10.3354/ab00287
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of omnivorous fish and nutrient loading on net productivity regulation of phytoplankton and periphyton

Abstract: Top predators and nutrient loading are key components in the regulation of community structure and biomass in aquatic ecosystems. However, few studies have addressed how these 2 components interact to determine metabolic variables of the community, such as oxygen production and respiration rates. The pelagic zone has been the focus of most research on trophic cascades. Nevertheless, recent data increasingly show the importance of periphyton to the functioning of lakes. We conducted a fully factorial field expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…This species is typically omnivorous, and an extensive stomach content analysis of resident fish captured in Lake Cabiúnas revealed a diet consisting of both primary producers, such as algae (mainly from classes Bacillariophyceae and Zygnemophyceae) or cyanobacteria, and herbivores, such as zooplankton (mainly phylum Rotifera and classes Branchiopoda, Maxillopoda, and Ostracoda) or snail larvae (Coutinho et al 2000). Yellow tetra in Lake Cabiúnas may also feed selectively on periphyton depending on the phytoplankton community (Guariento et al 2010). Fish were captured and kept for 24 h in a cage submerged in the lake, following which they were added to the mesocosms (?Fish and ?Nutr?Fish conditions, respectively) at densities often observed in situ [13 individuals (ind.)…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…This species is typically omnivorous, and an extensive stomach content analysis of resident fish captured in Lake Cabiúnas revealed a diet consisting of both primary producers, such as algae (mainly from classes Bacillariophyceae and Zygnemophyceae) or cyanobacteria, and herbivores, such as zooplankton (mainly phylum Rotifera and classes Branchiopoda, Maxillopoda, and Ostracoda) or snail larvae (Coutinho et al 2000). Yellow tetra in Lake Cabiúnas may also feed selectively on periphyton depending on the phytoplankton community (Guariento et al 2010). Fish were captured and kept for 24 h in a cage submerged in the lake, following which they were added to the mesocosms (?Fish and ?Nutr?Fish conditions, respectively) at densities often observed in situ [13 individuals (ind.)…”
Section: Experimental Designmentioning
confidence: 99%
“…Yellow tetra (Hyphessobrycon bifasciatus; family Characidae) is a widely distributed fish species in inland waters in Brazil and is abundant in the lake that is the focus of the study reported here (Coutinho et al 2000). The potential effects of yellow tetra on the CO 2 balance in aquatic ecosystems are difficult to predict, since this species feeds on both herbivores (zooplankton) and primary producers (algae) in the food web (Coutinho et al 2000;Guariento et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…example, to Fragilariaceae may be expected, as their abundance correlated negatively with fish abundance. The direct periphytic biomass consumption by omnivorous fish was showed in experimental study by Guariento et al (2010). Blanco et al (2008) showed that zooplanktivorous fish enhanced the abundance of Euglenophyceae and Zygnematophyceae, as well as algal species richness and diversity, by secreting biogenic substances.…”
Section: Parametersmentioning
confidence: 98%
“…Grazing pressure may be very important biotic factor shaping epiphyton assemblages (Abe et al, 2007;Guariento et al, 2010;Tarkowska-Kukuryk, 2013). In the studied lakes, the pressure from fish grazing (with S. erythrophthalmus as the most significant species) could affect epiphytic algae, particularly in Lake Krzczeń, with the highest fish abundance.…”
Section: Parametersmentioning
confidence: 98%
See 1 more Smart Citation